Development of Spray Pyrolysis System for Deposition of Nano-structure Materials - Son, Vuong; Chien, Nguyen Duc; Toan, Truong Thanh; Anh, Doan Tuan; Tuan, Mai Anh; Thuy, Luong Thi Thu; Thanh, Pham Thi Kim (Communications in Physics, 2015)
In this paper, we report the development of the spray pyrolysis technique for preparing different nano-structure materials toward the application in thin film solar cells. The spray pyrolysis system can heat up the substrate to 6000C with less than 0.01% full scale. The ramping rate can be set to 100C per minute. The effective coating area can be up to 100 x 100 mm2. Using this technique, the thickness and roughness of the films can be controlled. The obtained morphology, the microstructure of the thin-films, given by scanning electron microscope, X ray diffraction…showed that the system is suitable for deposition of different layers of the dye sensitized solar cell.